Illegal forest activities in Berau and Kutai Timur: impacts, driving forces and remedies - Obidzinski, K.; Andrianto, A.; Hernawan, D.; Belle, C.W.; Kusumawati, R. (Center for International Forestry Research, 2006)
This brief provide information on a study that examines illegal forest activities in Berau and East Kutai Districts in Indonesia’s East Kalimantan province. By analyzing all types of extractive and processing forestry activities, the study identifies illegalities associated with these operations and assesses their economic, social/livelihood and environmental impacts. It also identifies the key driving forces behind illegal forest activities and proposes corrective measures.